1991
DOI: 10.1172/jci115284
|View full text |Cite
|
Sign up to set email alerts
|

Human appendix B cells naturally express receptors for and respond to interleukin 6 with selective IgA1 and IgA2 synthesis.

Abstract: Past studies have shown that freshly isolated human B cells from peripheral blood and tonsils do not express IL-6 receptors (IL-6R); however, mitogen or antigen activation of these B cells induces IL-6R and responsiveness to IL-6. In this study, we have shown that a high proportion of B cells enzymatically dissociated from human appendix, a gut-associated lymphoreticular tissue (GALT), expresses the IL-6R, and that recombinant human IL-6 induces significant increases in the number of Ig-producing cells. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(38 citation statements)
references
References 26 publications
2
35
1
Order By: Relevance
“…22 In the gut mucosa IL-6 regulates mucosal total protein synthesis, as well as IgA production by Peyer's patch B cells, and induces an increase in the number of IgA-producing cells in B cells of the human appendix. 23,24 This might explain our earlier findings that LGG treatment resulted in an increase in fecal IgA levels in infants with IgE-associated CMA. 25 IL-6 also acts on endothelial cells to promote upregulation of sICAM-1 and sE-selectin.…”
Section: Discussionmentioning
confidence: 69%
“…22 In the gut mucosa IL-6 regulates mucosal total protein synthesis, as well as IgA production by Peyer's patch B cells, and induces an increase in the number of IgA-producing cells in B cells of the human appendix. 23,24 This might explain our earlier findings that LGG treatment resulted in an increase in fecal IgA levels in infants with IgE-associated CMA. 25 IL-6 also acts on endothelial cells to promote upregulation of sICAM-1 and sE-selectin.…”
Section: Discussionmentioning
confidence: 69%
“…IL-6 markedly and selectively enhances IgA production in vitro by isotype-committed B cells (21,29). It has been reported that mice with targeted disruption of the gene encoding IL-6 mount very poor IgA responses in the intestine and lungs, but that this defect can be overcome following vector-directed IL-6 gene therapy (22).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally thought that IgA is predominant in mucosal areas (18,32) and that IgG mainly provides systemic protection. However, recent studies have shown that in both adenoids and tonsils, IgG-secreting cells are predominant (6), which is different from the main induction and effector sites in the gastrointestinal tract (i.e., Peyer's patches and the lamina propria), where the majority of B cells secrete IgA (18,32). The large numbers of IgG-and IgA-secreting cells in the epithelial and subepithelial compartments of adenoids and tonsils suggest that they have characteristics of effector sites and that IgG could be a significant component of local mucosal responses (6).…”
Section: Discussionmentioning
confidence: 99%